Development of monoclonal antibodies against Hantaan virus nucleocapsid protein. - Ha, I S (1995)
Forty-five hybridoma cell lines producing monoclonal antibodies against Hantaan virus, the etiologic agent of hemorrhagic fever with renal syndrome, were generated by fusion of P3-X63-Ag8.V653 myeloma cells with spleen cells of mice immunized with inactivated Hantaan virus vaccine. Among these, 38 antibodies were identified as binding to the 48-kDa nucleocapsid protein by immunoblot assay or radioimmunoprecipitation. Twenty-six of them were of the immunoglobulin G1 (IgG1), nine were of the IgG2a, and three were of the IgA isotype. According to cross-reactivities with other serotypes of the genus Hantavirus, the antibodies were classified into three groups: 6 antibodies specific to the Hantaan serotype (group I), 20 antibodies cross-reacting with Hantaan and Seoul serotypes (SR-11, Tchoupitoulas, and R22) (group II), and 12 antibodies cross-reacting with Hantaan, Seoul, and Prospect Hill serotypes (group III). None of the antibodies cross-reacted with the Puumala serotype. With a panel of antibodies of different cross-reactivities, serotypes of Hantavirus could be differentiated. Thirty-eight monoclonal antibodies against Hantaan virus nucleocapsid protein which have different cross-reactivities between serotypes were developed. These results confirmed the presence of multiple serotype-specific epitopes on the nucleocapsid protein of Hantaan virus, which can be utilized in differentiation of serotypes.